Kontaminasi Bakteri Coliform pada Es Kelapa Muda di Kota Bengkulu - Rica Denis (Lembaga Pengembangan Kinerja Dosen, 2026)
Young coconut ice is one of the most frequently consumed ready-to-drink beverages among urban communities because it is inexpensive, refreshing, and widely available from street vendors. Nevertheless, the serving process generally involves added water, ice cubes, sweeteners, repeated use of utensils, open storage, and direct contact with food handlers. These conditions can increase the probability of microbiological contamination, particularly when sanitation and personal hygiene are not consistently maintained. Coliform bacteria are used as sanitation indicators because their presence reflects possible contamination from water, ice, equipment, handlers, or the surrounding selling environment. This descriptive laboratory study aimed to identify Coliform contamination in young coconut ice sold along Depati Payung Negara Street, Bengkulu City. Three samples were obtained through total sampling and analyzed in the Microbiology Laboratory of Akademi Analis Kesehatan Harapan Bangsa Bengkulu using the Most Probable Number (MPN) method, consisting of presumptive, confirmatory, and completed tests. The examination used Lactose Broth, Brilliant Green Lactose Bile Broth, Nutrient Agar, biochemical media, and Gram staining. The results showed that one sample was positive for Coliform with an MPN index of 265 cells/100 mL. Completed testing indicated Gram-negative bacilli with biochemical characteristics consistent with non-fecal Coliform, namely Enterobacter aerogenes. The findings emphasize the need for improved control of water and ice quality, utensil sanitation, food-handler hygiene, and routine monitoring of street beverages to minimize potential public health risks.